Vampiros na literatura: limites do gênero fantasia na série Twilight - Arantes, Judith Tonioli (2010)
Being part of the human imaginary, the vampires found their way into literature in the end of the eighteenth century, and remained there throughout the nineteenth century, being the climax of the narratives they were present known as Dracula, written by Bram Stoker. Over the twentieth century, the vampires experienced moments of fame in literature, through works such as Anne Rice s The vampire Chronicles; in the movies, through makings and remakings of Bram Stoker s Dracula and other vampires from TV series, such as Blade , and the movie made based on Anne Rice s Interview with the vampire. In the beginning of the twenty-first century, a North American author wrote a series of four books, the Twilight series, which constitute a dialogue with the literary myth crystallized by Bram Stoker s Dracula. Such dialogue, though considered to be intentionally denying the previous literary myth, confirms it in a number of ways. In order to study the presence of the literary myth in Stephenie Meyer s works, it is first necessary to study the possible origins of the myth in the human imaginary, moving, then, to a study of the types of narratives in which the vampires are present in literature, such as the fantastic, a mode found in fantasy, a literary gender. Once the possible origins and types of narrative are studied, it is possible to analyze the vampire myth renewed presented by Stephenie Meyer and the relation between her work, the Twilight series, and the fairy stories.